Synthesis, Characterization, Thermal Analysis, DFT, and Computational/Anti-Corrosion Studies for New Azo Metal Complexes - Jarallah, Hanadi Mahdi; Ali, Safaa Hussein (Indonesian Journal of Chemistry, 2025)
Two new azo-substituted ligands (L1 and L2) were synthesized in a two-step reaction involving condensation between diazonium salt and hydroxyanisole. L1 is (E)-2-(tert-butyl)-6-((4-chlorophenyl)diazenyl)-4-methoxyphenol, and L2 is (E)-2-((3-(tert-butyl)-2-hydroxy-5-methoxyphenyl)diazenyl)benzoic acid. These ligands were employed to synthesize four new bidentate azo metal complexes [MCl2(Lx)] (x = 1 or 2, M = Ni(II) or Cu(II)). The prepared compounds were characterized using various structural analysis techniques, including IR, EI-mass, 1H-NMR, 13C-NMR, and thermogravimetric analysis (TGA). The results confirmed that the ligands coordinate to the metal ion in a bidentate manner through the nitrogen atom of the azo group, the deprotonated phenolic oxygen in the case of L1, and the carboxylic oxygen in the case of L2. A theoretical study was also performed to predict the chemical reactivity and stability of the prepared ligands and their metal complexes. A set of mathematical calculations was employed to describe the full geometry optimizations using density functional theory (DFT), including chemical hardness (η), electronic chemical potential (μ), and electronegativity (χ). The small energy gap calculated between the highest occupied molecular orbital and least unoccupied molecular orbital energies indicates charge transfer within the complexes. These computational calculations suggest that the title compounds are promising candidates as corrosion inhibitors.